Connexins and Aging-Associated Respiratory Disorders: The Role in Intercellular Communications - Tatiana Zubareva; Ekaterina Mironova; Anna Panfilova; Yulia Krylova; Gianluigi Mazzoccoli; Maria Greta Pia Marasco; Igor Kvetnoy; Peter Yablonsky (Biomedicines)
This article reviews the contemporary understanding of the functional role of connexins in intercellular communications, their involvement in maintaining cellular and tissue homeostasis, and in aging-associated respiratory disease pathogenesis. Connexins are discussed as potential therapeutic targets. The review particularly focuses on the involvement of gap junction connexins and hemichannels in the transfer of calcium ions, metabolite molecules, ATP, and mitochondria through the cell membrane. Various disorders in the regulation of intercellular communication can heavily contribute to the pathogenesis of multiple diseases, including respiratory system diseases. A deeper understanding of molecular mechanisms underlying the activities of various connexins in gap junction channels will enable the prospective development of therapeutic approaches by either inhibiting or stimulating the activities of a certain connexin, while considering its critical functions in intercellular communications on the whole.